Method for displaying grain size of 9Cr18 martensitic stainless steel

By using corrosion agents composed of hydrochloric acid, sulfuric acid, nitric acid and anhydrous ethanol, 9Cr18 martensitic stainless steel is corroded, which solves the problem of poor corrosion effect in the existing technology, and achieves high-accurate grain size detection and avoids Restrictions on the use of picric acid.

CN119000225BActive Publication Date: 2025-02-25SHANGHAI SHANGZHOU BEARING QUALITY INSPECTION INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411487629.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-25
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing saturated aqueous solution corrosion agent of picric acid is poor in the grain size corrosion of 9Cr18 martensitic stainless steel, resulting in large deviations in the detection results. The purchase of picric acid has been banned and is difficult to replace.

Method used

Using a corrosive agent composed of hydrochloric acid, sulfuric acid, nitric acid and anhydrous ethanol, a corrosive agent with a H+ molar concentration of 2.0 mol/L -6.0 mol/L was prepared by adjusting the proportion and concentration of each component to corrode 9Cr18 martensite. Stainless steel, corrosion time is 80-120 seconds.

Benefits of technology

It realizes a clear display of the grain size of 9Cr18 martensitic stainless steel, improves the accuracy and stability of the detection results, extends the service life of the corrosive agent, and avoids the limitations of the use of picric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119000225B_ABST
    Figure CN119000225B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metallographic structure detection, and in particular relates to a method for displaying the grain size of 9Cr18 martensitic stainless steel, the method comprising: adding 40 to 60 parts by mass of hydrochloric acid, 6 to 7 parts of sulfuric acid and 5 to 7 parts of nitric acid to 30 to 40 parts of anhydrous ethanol to obtain an etchant; placing a prepared 9Cr18 martensitic stainless steel sample to be detected into the etchant and shaking it, corroding it for 80-120 seconds, and taking out the sample after the surface of the sample turns yellow. The corrosion method can completely and clearly display the grain boundary of 9Cr18 martensitic stainless steel. The invention makes the corrosion process precisely controllable, so that the display of the grain size is not subject to deviation caused by corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallographic structure detection, and in particular relates to a method for displaying the grain size of 9Cr18 martensitic stainless steel. Background Art

[0002] 9Cr18 is the most common stainless steel for bearings. It has high strength, high hardness, wear resistance and good corrosion resistance. It is widely used in bearing materials that require corrosion resistance. The grain size grade has a close correlation with the strength and toughness of the bearing. Therefore, the grain size grade test is included in the test items for its analysis and acceptance.

[0003] Currently, the more commonly used corrosive agent for displaying the grain size of 9Cr18 martensitic stainless steel is: saturated aqueous solution of picric acid + appropriate amount of buffer (one of which is sodium dodecylbenzene sulfonate).

[0004] Moreover, the corrosive agent is a general grain size corrosion solution for martensitic stainless steel. Due to the existing technical level, there has been no better alternative corrosion solution. However, due to the technical characteristics of the solution itself, its corrosion effects such as uniformity and martensitic grain boundary display are not satisfactory. It is even more difficult to achieve the purpose of accurate detection of the martensitic grain size corrosion effect of 9Cr18 and other stainless steels. The corrosion grain boundaries are blurred and uneven, the grain boundaries are not fully displayed and not clear enough, and the test results have large deviations and cannot truly reflect the actual grain size grade of the sample. At the same time, due to the technical characteristics of the corrosive agent itself, the corrosion rate is difficult to control, and the corrosive agent is not stable enough. After corroding multiple samples, the corrosion effect is worse, or even impossible to corrode. After the corrosive agent is stored for a certain period of time, the corrosive agent is very likely to fail, which brings inconvenience to the detection. In recent years, due to environmental protection and safety considerations, picric acid has been banned from purchase. Summary of the invention

[0005] The method for displaying the grain size of 9Cr18 martensitic stainless steel provided by the present invention can solve the technical problem that the corrosive agent is a general grain size corrosion solution for martensitic steel, the picric acid corrosion method replaced by the picric acid corrosion method has a poor corrosion effect on the grain size of 9Cr18 martensitic stainless steel, the corrosion structure is fuzzy and uneven, and the grain boundary edge is not clearly displayed, resulting in a large deviation in the detection result, and in recent years, due to environmental protection and safety considerations, picric acid has been banned from purchase.

[0006] The solution provided by the embodiment of the present invention is as follows:

[0007] A method for displaying the grain size of 9Cr18 martensitic stainless steel, the method comprising:

[0008] Add 40 to 60 parts by weight of hydrochloric acid, 6 to 7 parts by weight of sulfuric acid, and 5 to 7 parts by weight of nitric acid to 30 to 40 parts by weight of anhydrous ethanol to obtain a corrosive agent;

[0009] Place the prepared 9Cr18 martensitic stainless steel sample to be tested into the corrosive agent and shake it for 80-120 seconds. Take out the sample after the surface of the sample turns yellow.

[0010] In an optional embodiment, the H of the etchant + The molar concentration is 2.0 mol / L -6.0 mol / L.

[0011] In an optional embodiment, the corrosion time is 80 seconds to 120 seconds.

[0012] In an optional embodiment, the mass concentration of the hydrochloric acid is 36%-38%, the mass concentration of the sulfuric acid is 95%-98%, the mass concentration of the nitric acid is 65%-68%, and the mass concentration of the anhydrous ethanol is >99%.

[0013] In an optional embodiment, the method further includes: heat-preserving the 9Cr18 stainless steel at 1050°C-1080°C for 20 min-30 min in a box furnace, oil-cooling the 9Cr18 stainless steel with a quenching oil temperature not higher than 60°C, performing deep freezing treatment at -70°C, and tempering at 180°C for two hours to obtain the 9Cr18 martensitic stainless steel to be tested;

[0014] Cleaning the 9Cr18 martensitic stainless steel to remove the oil stains and oxidized structures on the surface of the 9Cr18 martensitic stainless steel, and obtaining a sample to be tested and analyzed;

[0015] The sample to be tested and analyzed is sampled along the longitudinal section direction, and after sampling, the sample is hot mounted to remove burrs, and the sample is coarsely ground using metallographic sandpaper of a first frosting degree, finely ground using metallographic sandpaper of a second frosting degree, and then polished with a 0.5 μm diamond polishing agent.

[0016] In an optional implementation, the first frosting degree is smaller than the second frosting degree, the first frosting degree Ra is 12.5-100, and the second frosting degree Ra is 0.1-6.3.

[0017] In an optional embodiment, the grain size grade of the 9Cr18 martensitic stainless steel corroded by the grain boundary is above grade 3.5.

[0018] In an optional embodiment, the grinding speed is 200-400 r / min, and the polishing speed is 1000-1400 r / min.

[0019] In an optional embodiment, the coarse grinding time is 2-3 minutes, the fine grinding time is 4-5 minutes, and the polishing time is 2-3 minutes.

[0020] In an optional embodiment, after the sample is prepared, the sample is thoroughly cleaned with absorbent cotton and running water, and then sprayed with anhydrous ethanol for drying.

[0021] In an optional embodiment, the corrosion temperature of the corrosive agent is 15°C-30°C.

[0022] In an optional embodiment, the grain size grade of the 9Cr18 martensitic stainless steel corroded by the grain boundary is above grade 3.5.

[0023] The method for displaying the grain size of 9Cr18 martensitic stainless steel provided in the embodiment of the present invention has at least the following beneficial effects:

[0024] The method for displaying the grain size of 9Cr18 martensitic stainless steel provided in the embodiment of the present invention comprises preparing an etchant in step S101. The hydrochloric acid in the etchant has a good corrosion effect on the grain boundaries. At the same time, under the dilution of ethanol, the solution is weakly acidic and has poor corrosion to the matrix structure. The complete grain boundary structure of the sample after corrosion can be clearly observed under a microscope. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] This specification describes the complete and instructive disclosure of the present application, including its best mode of implementation, for those skilled in the art. This specification refers to the accompanying drawings, in which:

[0026] Figure 1 A schematic flow chart of a method for displaying grain boundaries of 9Cr18 martensitic stainless steel subjected to grain boundary corrosion provided by the present invention.

[0027] Figure 2 The grain boundary display effect of 9Cr18 martensitic stainless steel with grain boundary corrosion provided by the present invention Figure 1 .

[0028] Figure 3 The grain boundary display effect of 9Cr18 martensitic stainless steel with grain boundary corrosion provided by the present invention Figure 2 .

[0029] Figure 4 This is a comparative example showing the effect of the 9Cr18 grain boundary after being corroded by a saturated aqueous solution of picric acid. DETAILED DESCRIPTION

[0030] Now with reference to the embodiments of the present application in detail, one or more examples of the embodiments of the present application are illustrated in the drawings. Each example is provided to explain the present application, but not to limit the present application. In fact, it will be clear to those skilled in the art that various modifications and changes can be made in the present application without departing from the scope or spirit of the present application. For example, the features described or described as a part of an embodiment can be used together with another embodiment to produce another embodiment. As used in this specification, the terms "first", "second", etc. are used interchangeably to distinguish one component from another component without intending to indicate the position or importance of each component. As used in the specification, unless the context clearly indicates otherwise, the terms "one", "an", "the", and "said" are intended to indicate that there are one or more elements. The terms "include", "include" and "have" are intended to be inclusive, and mean that there may be other elements in addition to the listed elements.

[0031] See also Figure 1 , an embodiment of the present invention provides a method for displaying the grain size of 9Cr18 martensitic stainless steel, the method comprising:

[0032] Step S101, adding 40 to 60 parts by mass of hydrochloric acid, 6 to 7 parts by mass of sulfuric acid and 5 to 7 parts by mass of nitric acid to 30 to 40 parts by mass of anhydrous ethanol to obtain an etchant.

[0033] Step S102: Place the prepared 9Cr18 martensitic stainless steel sample to be tested into the corrosive agent and shake it for 80-120 seconds, and take out the sample after the surface of the sample turns yellow.

[0034] In an optional implementation, after the sample to be tested and analyzed is prepared, it is thoroughly cleaned with absorbent cotton and running clean water, and then sprayed with anhydrous ethanol for drying.

[0035] In the embodiment of the present invention, the 9Cr18 martensitic stainless steel sample to be tested is placed in the corrosive agent, and the non-test surface of the sample to be tested and analyzed is clamped and slightly shaken for better corrosion effect. When the test surface appears dark yellow, the sample is taken out and fully cleaned and dried before observation. In the embodiment of the present invention, an optical microscope is used to observe the sample and detect its grain grade.

[0036] In the method provided in the embodiment of the present invention, hydrochloric acid has a good corrosion effect on grain boundaries. At the same time, under the dilution of ethanol, the solution is weakly acidic and has poor corrosion to the matrix structure. The corrosion effect is controllable, and the complete grain boundary structure of the sample after corrosion can be clearly observed under a microscope.

[0037] The embodiment of the present invention makes the corrosion process precisely controllable, that is, the corrosion process can be precisely controlled according to the need to display the grain size of 9Cr18 martensitic stainless steel, so that the surface tissue corrosion of the sample is within a controllable range, and the grain size grade of the sample after corrosion can be accurately detected. The embodiment of the present invention improves the accuracy and clarity of the grain size display of 9Cr18 martensitic stainless steel. In addition, the embodiment of the present invention further optimizes the performance of the corrosive agent and the corrosive agent by adjusting the amount of each component in the corrosive agent, prolongs the service life of the corrosive agent, and improves the stability and consistency of the corrosion effect.

[0038] The mass parts of hydrochloric acid in the corrosive agent can be 40 parts, 41 parts, 52 parts, 5 parts, 54 parts, 58 parts, 59 parts or 60 parts, etc.; the mass parts of sulfuric acid can be 6 parts or 7 parts, etc.; the mass parts of nitric acid can be 5 parts, 6 parts or 7 parts, etc., and the mass parts of anhydrous ethanol can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, etc.

[0039] In the embodiment of the present invention, the embodiment of the present invention can adjust the corrosion effect on the grain boundary of the 9Cr18 martensitic stainless steel to be detected by adjusting the value of the H+ molar concentration of the corrosive agent. Exemplarily, the value of the H+ molar concentration of the corrosive agent can be adjusted according to the detection requirements of the grain size of the 9Cr18 martensitic stainless steel to be detected (for example, the grain size level requirement is above level 5) to achieve the optimal corrosion effect on the sample surface, the grain boundary is displayed intact, and the grain size above level 5 can be detected.

[0040] In an alternative embodiment, the H of the etchant + The molar concentration is 2.0 mol / L-6.0 mol / L. For example, the H+ molar concentration of the corrosive agent may be 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, 5.0 mol / L or 6.0 mol / L, etc. In the embodiment of the present invention, by setting the corrosive agent within the above range, a good corrosion effect can be achieved on the grain boundary of 9Cr18 martensitic stainless steel.

[0041] Furthermore, the embodiment of the present invention can adjust the concentration or dosage of hydrochloric acid, sulfuric acid and nitric acid in the corrosive agent to adjust H + The molar concentration of the corrosive H + The molar concentration value is within the above range.

[0042] In an optional embodiment, the corrosion time is set to 80 seconds to 120 seconds.

[0043] Exemplarily, the 9Cr18 martensitic stainless steel to be tested is placed in a corrosive agent for corrosion for 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 110 seconds or 120 seconds, etc., to display the grain boundaries of the 9Cr18 martensitic stainless steel.

[0044] In an optional embodiment, the mass concentration of hydrochloric acid is 36%-38%, the mass concentration of sulfuric acid is 95%-98%, the mass concentration of nitric acid is 65%-68%, and the mass concentration of anhydrous ethanol is >99%.

[0045] For example, the mass concentration of hydrochloric acid can be 36%, 37% or 38%, etc. The mass concentration of sulfuric acid can be 95%, 96%, 97% or 98%, etc. The mass concentration of nitric acid can be 65%, 66%, 67% or 68%, etc. The mass concentration of anhydrous ethanol can be 99.1%, 99.3%, 99.4%, 99.6% or 99.7%, etc. The mass concentrations of the above components in the embodiments of the present invention are not limited to times.

[0046] In an optional embodiment, the method provided by the embodiment of the present invention also includes step S103, keeping the 9Cr18 stainless steel at 1050℃-1080℃ in a box furnace for 20 min-30 min, oil cooling with quenching oil with an oil temperature not higher than 60℃, deep freezing treatment at -70℃, and tempering at 180℃ for two hours to obtain the 9Cr18 martensitic stainless steel to be tested.

[0047] Step S104, cleaning the 9Cr18 martensitic stainless steel to remove the oil stains and oxidized structures on the surface of the 9Cr18 martensitic stainless steel to obtain a sample to be tested and analyzed.

[0048] Step S105, sampling the sample to be tested and analyzed along the longitudinal section direction, hot mounting the sample after sampling, removing burrs, coarse grinding the sample with metallographic sandpaper of the first frosting degree, fine grinding with metallographic sandpaper of the second frosting degree, and then polishing with 0.5μm diamond polishing agent.

[0049] In an optional embodiment, the method further includes: using 120# and 400# SiC metallographic sandpapers to perform rough grinding on the sample, and using 800# and 1200# SiC metallographic sandpapers to perform fine grinding on the sample, eliminating the wear marks produced during rough grinding, and preparing for polishing the sample surface. Then polishing is performed with a 0.5μm diamond polishing agent. The purpose of polishing is to remove the wear marks left on the metallographic surface due to fine grinding, so as to make it a smooth, traceless mirror surface. Among them, the meaning of "‌#" refers to the amount of abrasive per square inch. The higher the number, the finer the abrasive.

[0050] In an optional embodiment, the grinding speed is 200-400 r / min, and the polishing speed is 1000-1400 r / min.

[0051] In an optional embodiment, the coarse grinding time is 2-3 min, the fine grinding time is 4-5 min, and the polishing time is 2-3 min.

[0052] In an optional embodiment, after the sample is prepared, the sample is thoroughly cleaned with absorbent cotton and running water, and then sprayed with anhydrous ethanol for drying.

[0053] In an optional embodiment, the corrosion temperature of the corrosive agent is 15°C-30°C.

[0054] In an optional embodiment, the grain size level of the 9Cr18 martensitic stainless steel corroded by grain boundaries is above level 3.5.

[0055] The method for displaying the grain size of 9Cr18 martensitic stainless steel provided by the embodiment of the present invention will be further explained and described below through specific examples.

[0056] The chemical composition of the 9Cr18 martensitic stainless steel provided by the present invention comprises: a C content of 0.90-1.00%, a Si content of ≤0.80%, a Mn content of ≤0.80%, a P content of ≤0.035%, a S content of ≤0.020%, a Cr content of 17.0-19.0%, a Ni content of ≤0.25%, a Cu content of ≤0.25%, and Fe as the balance.

[0057] Example 1

[0058] 50 parts by mass of hydrochloric acid, 7 parts by mass of sulfuric acid and 7 parts by mass of nitric acid are added to 40 parts by mass of anhydrous ethanol to obtain a corrosive agent, and the solution is allowed to stand for 30 minutes.

[0059] The 9Cr18 stainless steel is kept at 1050-1080°C for 30 minutes in a box furnace, oil-cooled with quenching oil at an oil temperature not higher than 60°C, deep-cold treated at -70°C, and tempered at 180°C for two hours to obtain the 9Cr18 martensitic stainless steel to be tested. The 9Cr18 martensitic stainless steel is cleaned to remove oil stains and oxidized tissue on the surface of the 9Cr18 martensitic stainless steel to obtain the sample to be tested and analyzed.

[0060] The samples to be tested and analyzed are sampled along the longitudinal section direction. After sampling, the samples are hot-mounted to remove burrs. The samples to be tested and analyzed are coarsely ground with 120# and 400# SiC metallographic sandpapers, and finely ground with 800# and 1200# SiC metallographic sandpapers in turn to eliminate the wear marks produced during coarse grinding and prepare for the polishing of the sample grinding surface. Then polish with 0.5μm diamond polishing agent. The purpose of polishing is to remove the wear marks left on the metallographic grinding surface due to fine grinding, making it a smooth, traceless mirror surface. The coarse grinding time is 3min, the fine grinding time is 5min, and the polishing time is 3min. After the sample preparation is completed, the sample is thoroughly cleaned with absorbent cotton and running water, and then sprayed with anhydrous ethanol for drying.

[0061] Place the sample to be tested and analyzed in the above solution, place the test surface vertically, and corrode for 120 seconds. Clamp the non-test surface of the sample to be tested and analyzed and shake it slightly to improve the corrosion effect. When the test surface appears dark yellow, take out the sample to be tested and analyzed, and observe it after thorough cleaning and drying. Use a metallographic microscope to observe the grain boundaries of 9Cr18 martensitic stainless steel. The grain size of the 9Cr18 martensitic stainless steel corroded by the grain boundary line is 9.0. Detect its grain size as follows Figure 2 shown.

[0062] Example 2

[0063] 40 parts by mass of hydrochloric acid, 6 parts by mass of sulfuric acid and 2 parts by mass of nitric acid are added to 30 parts by mass of anhydrous ethanol to obtain a corrosive agent, and the solution is allowed to stand for 30 minutes.

[0064] The 9Cr18 stainless steel is kept at 1050-1080℃ in a box furnace for 20-30min, oil-cooled with quenching oil at an oil temperature not higher than 60℃, deep-cold treated at -70℃, and tempered at 180℃ for two hours to obtain the 9Cr18 martensitic stainless steel to be tested. The 9Cr18 martensitic stainless steel is cleaned to remove oil stains and oxidized tissue on the surface of the 9Cr18 martensitic stainless steel to obtain the sample to be tested and analyzed.

[0065] The samples to be tested and analyzed are sampled along the longitudinal section direction. After sampling, the samples are hot-mounted to remove burrs. The samples are coarsely ground with 120# and 400# SiC metallographic sandpapers, finely ground with 800# and 1200# SiC metallographic sandpapers, and then polished with 0.5μm diamond polishing agent. The coarse grinding time is 3min, the fine grinding time is 5min, and the polishing time is 3min. After the sample preparation is completed, the sample to be tested and analyzed is fully cleaned with absorbent cotton and running water, and then sprayed with anhydrous ethanol for drying.

[0066] Place the sample to be tested and analyzed in the above solution, place the test surface vertically, and corrode for 120 seconds. Clamp the non-test surface of the sample to be tested and analyzed and shake it slightly to improve the corrosion effect. When the test surface turns dark yellow, take out the sample, clean it thoroughly, and blow it dry before observation. Use a metallographic microscope to observe the grain boundaries of 9Cr18 martensitic stainless steel. The grain size of the 9Cr18 martensitic stainless steel corroded by the grain boundary line is 9.0. Detect its grain size as follows Figure 2 shown.

[0067] Example 3

[0068] Add 50 parts by mass of hydrochloric acid, 4 parts by mass of sulfuric acid and 5 parts by mass of nitric acid to 30 parts by mass of anhydrous ethanol to obtain a corrosive agent, and let it stand for 30 minutes.

[0069] The 9Cr18 stainless steel is kept at 1050-1080°C for 20-30min in a box furnace, oil-cooled with quenching oil at an oil temperature not higher than 60°C, deep-cold treated at -70°C, and tempered at 180°C for two hours to obtain the 9Cr18 martensitic stainless steel to be tested, and the 9Cr18 martensitic stainless steel is cleaned to remove oil stains and oxidized tissue on the surface of the 9Cr18 martensitic stainless steel.

[0070] The above-mentioned samples to be tested and analyzed are sampled along the longitudinal section direction. After sampling, the samples are hot-mounted to remove burrs. The samples are coarsely ground with 120# and 400# SiC metallographic sandpapers, and finely ground with 800# and 1200# SiC metallographic sandpapers in turn to eliminate the wear marks produced during coarse grinding and prepare for the polishing of the sample grinding surface. Then polish with 0.5μm diamond polishing agent. The grinding speed is 400r / min, and the speed during polishing is 1400r / min. The coarse grinding time is 2min, the fine grinding time is 4min, and the polishing time is 2min. The purpose of polishing is to remove the wear marks left on the metallographic grinding surface due to fine grinding, so as to make it a smooth, traceless mirror surface. After the sample preparation is completed, the sample is fully cleaned with absorbent cotton and flowing clean water, and then sprayed with anhydrous ethanol for drying to obtain the sample to be tested and analyzed.

[0071] Place the sample to be tested and analyzed in the above solution, place the test surface vertically, and corrode for 120 seconds. Clamp the non-test surface of the sample and shake it slightly to improve the corrosion effect. When the test surface turns dark yellow, take out the sample, clean it thoroughly, and blow it dry before observation. Use a metallographic microscope to observe the grain boundaries of 9Cr18 martensitic stainless steel and detect its grain size. The grain size of 9Cr18 martensitic stainless steel is 9.0. The grain size is as follows Figure 3 shown.

[0072] Comparative Example

[0073] The formula of the corrosive agent: 100ml of saturated picric acid solution; 2g of sodium dodecylbenzene sulfonate. After corrosion, add 2g of picric acid to 100ml of anhydrous ethanol, stir until it is fully dissolved, put it in a water bath at a constant temperature of 40℃, add 2g of sodium dodecylbenzene sulfonate, stir to dissolve, and let it stand for 30 minutes.

[0074] Corrosion method: First, prepare the corrosive agent according to the above method; then take the ground and polished 9Cr18 martensitic stainless steel material, wash and dry it, immerse it in the corrosive agent, soak it for 3 minutes, and take it out when the test surface turns dark yellow; use a metallographic microscope to detect the grain size of 9Cr18 martensitic stainless steel, such as Figure 4 shown.

[0075] Figure 2-Figure 3 The method provided in the embodiment of the present invention shows the effect of corroding the grain boundary of 9Cr18 martensitic stainless steel. Figure 4 This is the comparative example of the 9Cr18 grain boundary display effect after being corroded by a saturated aqueous solution of picric acid. Figure 2-Figure 3 Clear grain boundaries are shown. Figure 4 Some of the grain boundaries after corrosion treatment failed to achieve the expected effect. The grain boundaries were incomplete and not clear enough. It may also be due to technical defects of the corrosive agent itself. The corrosion rate is difficult to control, and the corrosive agent is not stable enough. After corroding multiple samples, the corrosion effect is worse or even impossible to corrode. The corrosive agent is very likely to fail after being stored for a certain period of time, which brings inconvenience to the detection.

[0076] This specification uses embodiments to disclose the present application, including the best embodiment, and also enables those skilled in the art to practice the present application, including making and using any device or system and performing any incorporated method. The embodiments of the present application and the technical solutions obtained by slightly changing the embodiments are all within the protection scope of the present application.

Claims

1. A method for displaying the grain size of 9Cr18 martensitic stainless steel, characterized in that: The method comprises: Add 40 to 60 parts by mass of hydrochloric acid, 6 to 7 parts by mass of sulfuric acid and 5 to 7 parts by mass of nitric acid to 30 to 40 parts by mass of anhydrous ethanol to obtain an etchant; wherein the mass concentration of the hydrochloric acid is 36% to 38%, the mass concentration of the sulfuric acid is 95% to 98%, the mass concentration of the nitric acid is 65% to 68%, and the mass concentration of the anhydrous ethanol is greater than 99%; Place the prepared 9Cr18 martensitic stainless steel sample to be tested into the corrosive agent and shake it for 80-120 seconds. Take out the sample after the surface of the sample turns yellow.

2. The method for displaying the grain size of 9Cr18 martensitic stainless steel according to claim 1, characterized in that: The H + The molar concentration is 2.0mol / L-6.0mol / L.

3. The method for displaying the grain size of 9Cr18 martensitic stainless steel according to claim 1, characterized in that: Also includes: S1: 9Cr18 martensitic stainless steel is kept at 1050℃-1080℃ in a box furnace for 20min-30min, oil-cooled with quenching oil at an oil temperature not higher than 60℃, deep-cold treated at -70℃, and tempered at 180℃ for two hours; S2: cleaning the 9Cr18 martensitic stainless steel treated by S1 to remove the oil stains and oxidized structures on the surface of the 9Cr18 martensitic stainless steel to obtain a sample to be tested and analyzed; S3: Sampling the 9Cr18 martensitic stainless steel treated by S2 along the longitudinal section direction, hot mounting the sample after sampling, removing burrs, coarse grinding the sample with metallographic sandpaper of the first frosting degree and fine grinding with metallographic sandpaper of the second frosting degree, and then polishing with a 0.5μm diamond polishing agent to obtain the prepared 9Cr18 martensitic stainless steel sample to be tested.

4. The method for displaying the grain size of 9Cr18 martensitic stainless steel according to claim 3, characterized in that: The first frosting degree is smaller than the second frosting degree, the first frosting degree Ra is 12.5-100, and the second frosting degree Ra is 0.1-6.

3.

5. The method for displaying the grain size of 9Cr18 martensitic stainless steel according to any one of claims 1 to 4, characterized in that: The corrosion temperature of the corrosive agent is 15°C-30°C.

6. The method for displaying the grain size of 9Cr18 martensitic stainless steel according to any one of claims 1 to 4, characterized in that: The grain size grade of the corroded 9Cr18 martensitic stainless steel is above grade 3.5.

Citation Information

Patent Citations

  • Metallographic corrosion method for martensitic precipitation hardening stainless steel crystal boundary

    CN102443803A

  • Target material corrosive agent and application method thereof

    CN111074279A